PENGARUH GAYA HIDUP, BRAND IMAGE, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN OPPO SMARTPHONE - Kezia Michelle Setiawan; Handoyo Djoko Waloejo (Jurnal Ilmu Administrasi Bisnis, 2018)
The need for communication is a very important thing for every community without exception. To support high human mobility at present, telecommunication facilities are needed that support the activities of working in daily life. This is supported by the desire of the community to have adequate and supportive telecommunications equipment in all lines. Strategies that can be carried out in the form of lifestyle, brand image, and word of mouth so as to encourage increased decision to purchase OPPO Smartphones. The type of research used is explanatory research. The sampling technique uses non-probability sampling method, the sample used in this study are students of the Faculty of Social and Political Sciences of Diponegoro University who use and have used OPPO Smartphone. Respondents in this study amounted to 100 respondents. The collection uses SPSS program assistance, which previously used validity test, reliability test, cross tabulation, correlation coefficient, determination coefficient, simple and multiple regression analysis, significance test (t test and F test). Measurement scale using Likert scale. The results showed that all variables in this study had a positive and significant influence on the dependent variable. This is indicated by the results of the multiple correlation coefficient test of 0.780. Significantly, lifestyle variables, brand image, and word of mouth have a positive effect indicated by the calculated F value greater than F table that is equal to 49.77> 2.70. The advice that can be given is that OPPO Smartphones should be able to continue to provide better quality or quality in the future, increasing the attractiveness of consumers in using OPPO Smartphones, and increasing the impression that OPPO Smartphones are suitable for use.